HISTORICAL PROSPECT ANALYSIS OF LEADERSHIP IN THE ERA OF THE CONQUEROR OF CONSTANTINOPLE IN THE BOOK MUHAMMAD AL FATIH 1453 BY FELIX Y. SIAUW - Huzaimi , Naswa; Khumaidi, Ahmad; Solihin, Mohamad (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
This study aims to examine the values of character education in the book Muhammad Al Fatih 1453 by Felix Y. Siauw and its relevance to Islamic religious education in the contemporary era. Using a qualitative approach through literature study and content analysis, this research highlights the aspects of religiosity, leadership, hard work, tolerance, and love for the country reflected in the figure of Sultan Mehmed II. These values not only reflect the superior character of a past Islamic leader, but are also relevant in shaping the personality of today's learners. This book illustrates that learning based on the history of Islamic figures can be an effective and contextual character learning strategy. In addition, Muhammad Al Fatih as a historical figure becomes a strong role model in the formation of morals, spirituality, and leadership vision. The relevance of these values to the Islamic Religious Education curriculum further emphasizes that character strengthening can be done through the integration of historical narratives into the educational process. Therefore, this study concludes that this book is very worthy of being used as a learning medium to strengthen the character of the younger generation in an applicable manner.